Essentials of management information systems - Laudon, Kenneth C. (Pearson/Prentice Hall, 2009)
These authoritative authors continue to define the MIS course by emphasizing how business objectives shape the application of new information systems and technologies and integrating a career orientation that demonstrates the relevance of information systems to all business students regardless of their major.